2001
DOI: 10.1051/forest:2001128
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter and nitrogen dynamics in a mature forest of common beech in the Sierra de la Demanda, Spain

Abstract: -Aboveground biomass, litterfall, leaf weight loss due to decomposition, N return and seasonal leaf N dynamics were studied in the Sierra de la Demanda, Spain, a Mediterranean climatic zone. The forest ecosystem considered was a climax beech (Fagus sylvatica L.) forest. Aboveground biomass was estimated by cutting and weighing seven trees from a beech stand according to diameter classes, recording the categories of trunk, branches and leaves. The results indicate a total biomass of 132.7 Mg ha -1 . The litterf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…These percentages are within the ranges reported by Caritat, García, Lapeña, and Vilar, (2006), Santa Regina (2000), Santa Regina and Tarazona (2001a) and Santa Regina and Tarazona (2001b), who found that leaves accounts for 50-80 % of all litwho found that leaves accounts for 50-80 % of all litterfall components in various ecosystems. Several studies (Domínguez, 2009;González et al, 2008;López et al, 2013;Rodríguez, 2010) reported leaf depositions ranging from 40-86 % in ecosystems similar to that used in the present study.…”
Section: Litterfallsupporting
confidence: 72%
“…These percentages are within the ranges reported by Caritat, García, Lapeña, and Vilar, (2006), Santa Regina (2000), Santa Regina and Tarazona (2001a) and Santa Regina and Tarazona (2001b), who found that leaves accounts for 50-80 % of all litwho found that leaves accounts for 50-80 % of all litterfall components in various ecosystems. Several studies (Domínguez, 2009;González et al, 2008;López et al, 2013;Rodríguez, 2010) reported leaf depositions ranging from 40-86 % in ecosystems similar to that used in the present study.…”
Section: Litterfallsupporting
confidence: 72%
“…Shifts in the time of litter fall result in the leaves (and another components) finding different conditions on the soil surface (microclimate, micro-organisms biomass etc.). Litter quality affects not only the rate of mass loss, but also the patterns and rates of nutrient immobilisation or release [38].…”
Section: Effect On Decompositionmentioning
confidence: 99%
“…У зависности од добијених модела, користе се друге једначине, у којима су, као независни параметри, D 2 H, HD 2 , итд., гдје је H -висина стабла у метрима (Nihlgård 1972;Duvigneaud et al 1977;Bartelink 1997;Pretzsch 2000;Le Goff and Ottorini 2000;Santa Regina and Tarazona 2001;Cienciala et al 2005;Calamini and Gregori 2013). Регресијски коефицијент тежи вриједности 2,67, док регресијска константа варира у зависности од еколошких услова (Zianis and Mencuccini 2004).…”
Section: гајење букових шумаunclassified